Specific marking of hESCs-derived hematopoietic lineage by WAS-promoter driven lentiviral vectors. - Pilar Muñoz (Public Library of Science (PLoS), 2012)
Genetic manipulation of human embryonic stem cells (hESCs) is instrumental for tracing lineage commitment and to studying human development. Here we used hematopoietic-specific Wiskott-Aldrich syndrome gene (WAS)-promoter driven lentiviral vectors (LVs) to achieve highly specific gene expression in hESCs-derived hematopoietic cells. We first demonstrated that endogenous WAS gene was not expressed in undifferentiated hESCs but was evident in hemogenic progenitors (CD45(-)CD31(+)CD34(+)) and hematopoietic cells (CD45(+)). Accordingly, WAS-promoter driven LVs were unable to express the eGFP transgene in undifferentiated hESCs. eGFP(+) cells only appeared after embryoid body (EB) hematopoietic differentiation. The phenotypic analysis of the eGFP(+) cells showed marking of different subpopulations at different days of differentiation. At days 10-15, AWE LVs tag hemogenic and hematopoietic progenitors cells (CD45(-)CD31(+)CD34(dim) and CD45(+)CD31(+)CD34(dim)) emerging from hESCs and at day 22 its expression became restricted to mature hematopoietic cells (CD45(+)CD33(+)). Surprisingly, at day 10 of differentiation, the AWE vector also marked CD45(-)CD31(low/-)CD34(-) cells, a population that disappeared at later stages of differentiation. We showed that the eGFP(+)CD45(-)CD31(+) population generate 5 times more CD45(+) cells than the eGFP(-)CD45(-)CD31(+) indicating that the AWE vector was identifying a subpopulation inside the CD45(-)CD31(+) cells with higher hemogenic capacity. We also showed generation of CD45(+) cells from the eGFP(+)CD45(-)CD31(low/-)CD34(-) population but not from the eGFP(-)CD45(-)CD31(low/-)CD34(-) cells. This is, to our knowledge, the first report of a gene transfer vector which specifically labels hemogenic progenitors and hematopoietic cells emerging from hESCs. We propose the use of WAS-promoter driven LVs as a novel tool to studying human hematopoietic development.